Employment decision of female spouses of Filipino overseas contract workers - Gatapia, Sophia Christianne M.; Dorado, Rowena A. (2016)
The Philippines holds the highest international rate of labor out-migration in Asia. However, overseas migration of urban Filipino household heads lowers the labor supply of female spouses left behind and increases consumption of leisure. This study used the 2012 merged data file of the Family and IncomeExpenditure Survey (FIES) and Labor Force Survey (LFS) to examine the extent to which male migration affects the labor force participation of their spouses through logistic and multinomial logistic regression analysis. Results show that remittances, age, place of residence, educational attainment and presence of dependent children, significantly influence a certain categorical employment decision. In self-employment, significance of age, place of residence and presence of dependent children is found to be more pronounced. On the other hand, in paid employment, it is the remittances r cried by these female spouses and their educational attainment that primarily affects their decision.
Keywords: Filipino foreign workers; Free choice of employment; Wives; Married women -- Employment